Photoluminescence of Mn2+ Centers in Chalcohalide Glasses - Yan, Qiqi; Liu, Yinyao; Chen, Guorong; Da, Ning; Wondraczek, Lothar (Journal of the American Ceramic Society, 2011)
We report on photoluminescence from Mn2+-doped chalcohalide glasses of the GeS_2–Ga_2S_3–CsCl system. Upon blue excitation at 447 nm, a broad emission band occurs in the green spectral range from 500 to 600 nm, indicating the presence of tetrahedrally coordinated Mn2+ species. When the Mn2+-concentration is increased up to 2 mol%, an increasingly intense secondary emission band evolves at about 610–660 nm. Meanwhile, the intensity of the green band decreases gradually and shifts toward the red, resulting a very flatten luminescence from 500 to 750 nm, which provides a promising white light emitting source. As for the origin of this unique luminescence behavior of Mn2+, it is proposed that the ligand coordination number of Mn2+ in the present chalcohalide glasses experiences a partial change from tetrahedral to octahedral coordination.
EAM Import::2019-03-12